Biological notes on a fungus-growing ant, Trachymyrmex cf. zeteki (Hymenoptera, Formicidae, Attini) attacked by a diverse community of parasitoid wasps (Hymenoptera, Diapriidae) - Pérez-Ortega, B. (2010)
A number of wasps in the family Diapriidae, subfamily Diapriinae (Proctotrupoidea), are parasitoids that specialize on ant larvae. These wasps are abundant and diverse in the Neotropics, but little is known about their biology. We studied parasitism rates by an array of diapriine wasps that attack the larvae of fungus-growing ants, Trachymyrmex cf. zeteki, in a single population (near Gamboa, Panama). Relatively little is known about the biology and natural history of these ants, so we also present data on colony size and nest architecture. We excavated 136 colonies in central Panama from June to September 2006, and 20 nests from July 2009. We reared six wasp morphotypes; two of them in the genus Mimopriella Masner and Garcia, one Oxypria Kieffer, two Szelenyiopria Fabritius and one Acanthopria Ashmead. The mean intensity of larval parasitism per ant colony was 33.9% (2006), and its prevalence across all ant populations was 27.2% (2006 and 2009). Parasitism rates were not positively correlated with host colony size. A single case of super-parasitism was documented in which two Oxypria males were reared from the same host larva.